(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Background: One of the key objectives of a medicolegal autopsy is to ascertain the exact time of death. Traditionally, the early and late postmortem changes are used to estimate the time since death. There is still a need to develop a suitable method to determine the time since death because these postmortem changes may be impacted by external as well as internal variables. The objective of the present study was to determine the correlation between the concentration of sodium, potassium, calcium, and phosphate in pericardial fluid after death and the passage of time. Material and Methods: A sample of pericardial fluid was collected from the deceased who was brought in for a medicolegal autopsy. The pericardial fluid’s electrolyte content primarily that of sodium, potassium, calcium, and phosphate, was assessed. Based on the amount of time since death, the deceased were grouped. To determine the relationship between the electrolyte concentration and the time since death, log transferred regression analysis was used, and regression formulas were created for each parameter. Results: Time since death was negatively correlated with sodium concentration. Potassium, calcium, and phosphate levels correlated positively with time since death. There was no significant variation in electrolyte concentration between males and females. Between the age categories, there was no discernible variation in sodium, potassium, or phosphate levels. Conclusion: The measurement of electrolyte levels in the pericardial fluid following death suggested that the change in electrolyte level direction, whether rise or decrease, persisted for at least 36 hours and maybe up to 48 hours after death. Following that, the changing trend swung the other way. The time since death can be estimated by the electrolyte levels in the pericardial fluid.